2003
DOI: 10.1159/000072064
|View full text |Cite
|
Sign up to set email alerts
|

Protection of the Liver by Ischemic Preconditioning: A Review of Mechanisms and Clinical Applications

Abstract: Ischemic preconditioning refers to the endogenous mechanism of protection against a sustained ischemic insult following an initial, brief ischemic stimulus. Ischemia-reperfusion injury of the liver is a major cause of morbidity and mortality in liver surgery and transplantation and ischemic preconditioning is a promising strategy for improving the outcome of liver surgery. The preconditioning phenomenon was first described in a canine model of myocardial ischemia-reperfusion injury in 1986 and since then has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
80
0
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(90 citation statements)
references
References 73 publications
(127 reference statements)
3
80
0
4
Order By: Relevance
“…NHBD programs have been used successfully in kidney transplantation, and were able to increase donor pool of kidneys by 40%. In the field of liver transplantation the use of livers from NHBD shows a less favorable clinical results, because of the limited hepatic tolerance against warm ischemic damage compared with kidneys [28][29][30] . Although several clinical and experimental studies have shown that liver can compensate 60 min of WIT during liver resection [31,32] , in transplantation settings, there were few studies about limit of the period of warm ischemia before transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…NHBD programs have been used successfully in kidney transplantation, and were able to increase donor pool of kidneys by 40%. In the field of liver transplantation the use of livers from NHBD shows a less favorable clinical results, because of the limited hepatic tolerance against warm ischemic damage compared with kidneys [28][29][30] . Although several clinical and experimental studies have shown that liver can compensate 60 min of WIT during liver resection [31,32] , in transplantation settings, there were few studies about limit of the period of warm ischemia before transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…This has motivated a search for new approaches to reduce ischemic injury, among which ischemic preconditioning (IPC) constitutes a prominent promising strategy. This endogenous adaptive mechanism of protection against a sustained ischemic insult is afforded by exposure to an initial, brief ischemic stimulus followed by a period of reperfusion or by the administration of chemical agents, which is known as pharmacological preconditioning (PC) [2][3][4]. In livers, PC can reduce the release of transaminases, increase the survival of rodents after liver transplantation, and even improve human hepatic functions after major liver surgery in patients subjected to 30 min of ischemia [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In livers, PC can reduce the release of transaminases, increase the survival of rodents after liver transplantation, and even improve human hepatic functions after major liver surgery in patients subjected to 30 min of ischemia [5][6][7][8]. Furthermore, IPC decreases liver injury after both warm and cold I/R [2,4,9,10]. Several mechanisms have been proposed for protection by IPC, including activation of adenosine receptors [11][12][13][14], increased nitric oxide production [15], activation of protein kinase C [16], up-regulation of heat shock proteins, and increased antioxidant capacity [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Ischemic pre-conditioning (IPC) refers to brief episodes of ischemia followed by prolonged ischemia and reperfusion and has been shown to protect organs against ischemia/reperfusion injury [1] . Although, it was studied extensively in a variety of organs, including skeletal muscle, brain, spinal cord, kidney, intestine, heart and liver, the mechanisms of its protective effects remain unknown.…”
Section: Introductionmentioning
confidence: 99%